Trends in Islamic Education Management Studies, 2018- 2022 - Sulanam (Paedagogia: Jurnal Pendidikan, 2023)
This article discusses the trends in Islamic education management studies at UIN Sunan Ampel Surabaya and UIN Sunan Kalijaga Yogyakarta, as well as the factors driving these trends. After identifying the trends and their influencing factors, this research further proposes recommendations for bolstering Islamic education management studies. The analysis of these trends utilizes theses written by students of the Islamic education management study program at these two universities over five years, from 2018 to 2022. Considering that the theses are available online, the data in this study are sourced from the institutional repositories of both campuses. The data are classified into three study topics: management, leadership, and supervision. These topics are further categorized based on their study area, namely Islamic educational institutions. The data, presented in tables and graphs, are also supplemented with interviews with policy-makers. These interviews serve to delve deeper into the factors influencing the trends in studies. The research reveals a clustering of studies in certain sub-disciplinary areas, attributed to the tendencies in the supervisors' expertise and the availability of topics within the study program, which in turn shape the students' choices of thesis topics. Additionally, there is a factor of replication from previous studies conducted by former students.